Early and Midterm Results of Coronary Artery Bypass Grafting: an Emergency Center Experience - A. M. Khadjibaev; M. A. Obeid; A. A. Abdurakhmanov; O. A. Mashrapov; N. M. Rakhimov; I. A. Abdukhalimov; S. I. Sabirov; U. Sh. Ganiev (Ukrainian Journal of Cardiovascular Surgery, 2018)
This article is devoted to the analysis of immediate and mid-term outcomes of coronary artery bypass surgery. The study was conducted in the Republican Research Center for Emergency Medicine on 692 patients with multivessel coronary artery disease who underwent CABG surgery between 2013 and 2018 (female – 160 (23,1%), male – 532 (76,9%), mean age – 56,04±0,9 years). In most cases – 658 (95,1%) surgical revascularization was performed on a beating heart. Off-pump to on-pump conversion rate was 4,9%. The mean number of anastomoses was 3,6, early postoperative mortality rate was 2,5%, the risk factors for the lethal outcome were unstable hemodynamics at admission and conversion to on-pump due to emergency reasons. Actuarial survival rate during the 40 month follow-up was 97.3%. Freedom from recurrent angina and freedom from repeated revascularization was 90.8% and 98.2% respectively. Authors concluded that surgical revascularization of the myocardium in patients with multivessel coronary artery disease is accompanied by a low incidence of postoperative complications, a relatively low mortality in the early and mid-term periods of observation. CABG in our series accompanied by satisfactory indices of freedom from recurrent angina and freedom from revascularization.